1991
DOI: 10.1056/nejm199112193252503
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Performance of Computer Programs for the Interpretation of Electrocardiograms

Abstract: Our study shows that some but not all computer programs for the interpretation of ECGs perform almost as well as cardiologists in identifying seven major cardiac disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
1
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(155 citation statements)
references
References 25 publications
1
145
1
2
Order By: Relevance
“…The QT interval was calculated from the beginning of the QRS complex to the end of the T wave, using the validated Sicard 440/740 ECG computer-analysis programme (Megacart version 3 V4, 7/2.38/23; Siemens Elema) [25,26]. The QT intervals were then corrected for heart rate to obtain the QTc value using Bazett's formula [27].…”
Section: Methodsmentioning
confidence: 99%
“…The QT interval was calculated from the beginning of the QRS complex to the end of the T wave, using the validated Sicard 440/740 ECG computer-analysis programme (Megacart version 3 V4, 7/2.38/23; Siemens Elema) [25,26]. The QT intervals were then corrected for heart rate to obtain the QTc value using Bazett's formula [27].…”
Section: Methodsmentioning
confidence: 99%
“…16,17 The presence of a possible or definite myocardial infarction on the ECG was used as an indicator of presence of coronary artery disease. 18 Information on medical history of myocardial infarction, medical history, drug use, and smoking was obtained by a trained research assistant using a computerized questionnaire, which includes a Dutch version of the Rose questionnaire to determine the presence of angina pectoris and intermittent claudication.…”
Section: Cardiovascular Assessmentmentioning
confidence: 99%
“…Electrocardiographs that perform sophisticated signal processing and diagnostic interpretation of signals are today wide-spread [1]. Artificial neural networks (ANN's) are one of the most recent techniques in this field and have primarily been considered for classification of ECG's into different diagnostic groups [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Electrocardiographs that perform sophisticated signal processing and diagnostic interpretation of signals are today wide-spread [1]. Artificial neural networks (ANN's) are one of the most recent techniques in this field and have primarily been considered for classification of ECG's into different diagnostic groups [1], [2]. It has been shown that ANN's for specific issues can perform better than both experienced cardiologists and ruled-based criteria, e.g., in detecting acute myocardial infarction from the ECG [3].…”
Section: Introductionmentioning
confidence: 99%